The Use Of Blockchain Technology (Non-Fungible Tokens And Smart Contracts) In A Supply Chain Environment - A Framework - Mueller, Joerg Rene (Digital Repository of Theses, 2025)
Global supply chains are increasingly complex, often struggling with limited transparency, insecure data sharing, and inefficient processes. In response to these challenges, this research develops two novel blockchain-based artifacts—ProductNFT and ContainerNFT—that assign unique digital identities to products and containers, enabling authenticated lifecycle tracking and automated, near-real-time container and warehouse logistics management. These artifacts address existing gaps by enabling product authentication, strengthening origin, and enhancing operational agility, capabilities not currently offered by traditional SCM and PLM frameworks. Designed using Design Science Research (DSR) methodology and guided by Systems Theory, the work introduces two key artifacts: ProductNFT, which creates a secure, tamper-evident “digital twin” for each product, ensuring transparent lifecycle tracking and verifiable authenticity, and ContainerNFT, which employs smart contracts for automated container handling, improved inventory precision, and streamlined warehouse operations. Validated in a simulated multinational hydraulics production environment, these artifacts significantly improve inventory accuracy, expedite logistics coordination, and enhance quality control responsiveness. Beyond achieving operational gains, this research delivers a structured framework to address critical scalability, interoperability, and data privacy challenges in blockchain-enabled supply chains. The study underscores how private or consortium blockchain networks can enable secure, efficient, and compliant operations, advancing transparency, risk management, and strategic innovation by explicitly engaging SCM and PLM stakeholders and aligning with their needs. Overall, the findings underscore a strategic shift towards data-driven decision-making. By bridging the gap between blockchain’s theoretical promise and practical application, ProductNFT and ContainerNFT pave the way for more resilient, trusted, and future-ready supply chains and PLM systems, offering tangible benefits to industry practitioners and unlocking new opportunities for sustainable competitive advantage. Keywords: Blockchain Technology, Supply Chain Management, Product Lifecycle Management, Digital Twins, Non-Fungible Tokens, Smart Contracts, Design Science Research, Systems Theory